Playing With Code: An Innovative Way to Teach Numeracy and Early Math Concepts to Young DHH Children in the 21st Century. - Kritzer, Karen L.; Green, Laurie (American Annals of the Deaf)
While focusing on numeracy is essential in preschool classrooms with deaf and hard of hearing (DHH) children, it is also important that concepts of numeracy be taught in a way that incorporates executive functions, introduces computational thinking, and prepares students for life in a 21st-century world. Technology-enhanced teaching resources (e.g. Code-a-pillar, Bee-Bot, Kubo) provide coding opportunities that engage young children in problem solving, planning, and organization. These tools provide kinesthetic experiences in the exploration of early numeracy skills like counting, addition, subtraction, and estimation. The present article provides a rationale for including 21st-century teaching practices and educational technology resources in preschool classrooms with DHH children as one path toward strengthening early mathematics understanding. The authors also offer tips for teachers on how to select technology tools for classroom use and ways to integrate the use of these tools as part of meaningful mathematics instruction.